Effective Outcome Based Assessment Methodology for Laboratory Course in Engineering Education - Adamuthe, Amol C.; Mane, Sandeep U. (Journal of Engineering Education Transformations, 2016)
Outcome based education focus on outcomes and not the quality of inputs and process within institutions. This new trend strengthens the student learning and teaching quality. The major hurdle in implementation of OBE is lack of uniform and universally accepted methodology. This paper is an attempt to provide effective outcome-based assessment process which is more objective and minimizes ambiguity in implementation. The proposed methodology is applicable to laboratory courses in engineering education. Project based learning, direct attainment of course outcomes and up to 60 % reduction in assessment time are the strengths of proposed approach. Proposed methodology is applied to Database management systems laboratory course which is a third year computer science and engineering course. Evaluation plan with knowledge/skills addressed and mapping with Bloom’s taxonomy, experiment plan with deliverables, mapping with course outcomes and detailed assessment sheets with rubrics are presented.